Effectiveness of Self-Regulated Learning Intervention Program in Forethought Phase of a School Underachiever - Matitaputty, Eunike Karina Nadine; Kurniawati, Farida (Psychological Research on Urban Society, 2020)
When someone fails to achieve their potential, it is called underachievement. This phenomenon is predominantly observed for adolescent, particularly during the transition to middle school. This finding is observed because they are obligated to adapt to many internal and external changes. Several studies have confirmed that underachievement is caused by poor self-regulated learning skills. In this study, researchers adapted the Self-Regulation Empowerment Program (SREP) to help middle school student improve their self-regulation skills in learning. This program focuses on increasing the knowledge (cognitive domain) on self-regulated learning at the forethought phase by the means of SREP. This research adopts a single-case experimental design, particularly the A-B design. The analysis is performed by observing how well the participant performs in terms of success indicators, comparison between pretest and posttest scores, and qualitative analysis. Hence, the participant could achieve all success indicators in each session. This intervention program is effective in increasing knowledge on self-regulated learning at the forethought phase in empowerment and goal setting aspects. However, it is not effective in improving the time- management aspect. The procedures in this intervention can be adapted by parent and teachers to help the participant in improving their self-regulated learning ability.